STM probing of local oscillations of the Fano-Kondo effect: a Doniach-Sunjic approach for the Kondo peak - Seridonio, A. C.; Oliveira, L. N.; Yoshida, M. [UNESP] (Sociedade Brasileira de Física, 2009)
The use of the scanning tunneling microscope (STM) for the investigation of Kondo adatoms on normal metallic surfaces reveals a Fano-Kondo behavior of the conductance as a function of the tip bias. In this work, the Doniach-Sunjic expression is used to describe the Kondo peak and we analyze the effect of a complex Fano phase, arising from an external magnetic field, on the conductance pattern. It is demonstrated that such phase generates local oscillations of the Fano-Kondo line shape and can lead to the suppression of anti-resonances.
Keywords: STM (Scanning Tunneling Microscope); magnetic impurities; Kondo effect